Effect of Some Fungal Pathogen and Some Storage Treatments on Tomato and Cucumber Fruits Under Cold Storage (8? C) - Baghdad Science Journal (مجلة بغداد للعلوم)
In study carried out in the cold storage in college of Agric./Univ. of Baghdad at 8 ? C. shows that Alternaria , Pencillium , Rhizoctonia , Mucor , are the fungi that causes tomato fruits decay. This is the first record of Rhizoctonia and Mucor as a Tomato fruits rot under 8º c in Iraq. There is no fungal infection on cucumber fruits under 8 ? C. . Waxing tomato fruits reduced the severity of the fungi infection and gave shelflife (19 days) under 8 ? C. There is an infection with Mucor was found in tomato fruits kept in perforated polyethylene bages with 16 bores prevent the infection and the lowest severity and frequency of infection was found in waxed tomato fruits. Part of M.Sc thesis of the Second author.